If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (12x + -2) = (3x + 5) Reorder the terms: (-2 + 12x) = (3x + 5) Remove parenthesis around (-2 + 12x) -2 + 12x = (3x + 5) Reorder the terms: -2 + 12x = (5 + 3x) Remove parenthesis around (5 + 3x) -2 + 12x = 5 + 3x Solving -2 + 12x = 5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + 12x + -3x = 5 + 3x + -3x Combine like terms: 12x + -3x = 9x -2 + 9x = 5 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + 9x = 5 + 0 -2 + 9x = 5 Add '2' to each side of the equation. -2 + 2 + 9x = 5 + 2 Combine like terms: -2 + 2 = 0 0 + 9x = 5 + 2 9x = 5 + 2 Combine like terms: 5 + 2 = 7 9x = 7 Divide each side by '9'. x = 0.7777777778 Simplifying x = 0.7777777778
| (7x-4)=(5x+8) | | -5x+14=-1 | | (10x-12)=(4x+3)+(x+5) | | 18x^2+33x-216=0 | | (7x-13)=(2x+1)+(3x+2) | | 12x^2-47x-40=0 | | 22x-32=56 | | 2(x-1)-6=10(1-x)+6 | | y+0.1=-22.4 | | -5p+10+2p=-5 | | -1.5x^2-2.5x=0 | | -1.5x-2.5x=0 | | (2x+5)=(4x-35) | | x^2+48x+47=0 | | 6+3x+6x=-3+x+1+7x | | 8-2v-2=3-3v | | 7x-8-3x=24 | | 1+9=9+1 | | z+18=30 | | 10x+5Y=3621 | | 122-6x=21x+23 | | 122-6x=221x+23 | | 10-7x=30-14x | | -65-8x=8x+15 | | x^3-2x^2-3x=0 | | -42-3x=6-9x | | 9x^2+24x=-16 | | 3(2x+4)+8=50 | | ax=bx+c | | 4x^2=-12x+10 | | 10a-5b=12 | | x(4x^2-20x+24)=0 |